A Model of Supplier Selection Under Vendor Managed Inventory Contract - Zabrina Masud Mangka; Suparno Suparno; Erwin Widodo (Institut Teknologi Sepuluh Nopember, 2020)
VMI is the main concept for gaining accurate information and information sharing from customers to suppliers to achieve low safety stock levels, efficient inventory cost, and a reduction of ordering cost. There are many suppliers who supply spare part products under the VMI contract. Therefore, the company needs to make a decision for selecting a qualified supplier in order to improve customer service level and customer satisfaction. In addition, the uncertainty and vagueness of the expert's opinion is the prominent characteristic of the problem. Therefore an extensively used multi-criteria decision-making tool AHP can be utilized as an approach for supplier selection problems. This paper reveals the application of AHP model determining the best supplier with respect to selected criteria for selecting the best supplier under the VMI contract among the alternatives. There are criteria in this study namely quality, price, delivery, service, supplier’s background, and Information technology which include thirty subcriteria covers in the VMI contract. This research might be identified the critical criteria for supplier selection under the VMI contract.